EDUCATIONAL ROBOTICS APPLIED TO EARLY EDUCATIONAL STAGES - Verde, Ana; Valero, Jose Manuel (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Robots applied to education can offer us many advantages in the learning of students from the early educational stages, from the childhood stage. In addition to entertaining, they are a very powerful tool to motivate students and learn. Educational robotics in Early Childhood Education involves the initiation of computational thinking and support for the development of basic spatial notions (front, back, left, and right). In this paper, different activities are presented to develop spatial reasoning effectively. For the activities proposed we use the blue-bot robot as the application of educational robotics in a teaching and learning context. It is a small, very intuitive robot that draws the attention of children due to its attractive and transparent design. With this robot, programming languages consist only of five movement commands. With blue-bot robot in a playful way as a tool for the effective development of space rationing. This investigation is a qualitative research work, the application of robotic activities has been carried out with a sample of 21 children aged between 6-7 years. Five sessions were held, and participant observation was used in each session. After the application and considering the results and motivation of the young students, we can affirm that the activities and workshops were very beneficial to introduce basic spatial notions using educational robotics. Children showed connections between content learnings with valuable social practices through experiencing.